2021
DOI: 10.3390/molecules26226932
|View full text |Cite
|
Sign up to set email alerts
|

5-epi-Sinuleptolide from Soft Corals of the Genus Sinularia Exerts Cytotoxic Effects on Pancreatic Cancer Cell Lines via the Inhibition of JAK2/STAT3, AKT, and ERK Activity

Abstract: Pancreatic ductal adenocarcinoma is one of the most lethal malignancies: more than half of patients are diagnosed with a metastatic disease, which is associated with a five-year survival rate of only 3%. 5-epi-Sinuleptolide, a norditerpene isolated from Sinularia sp., has been demonstrated to possess cytotoxic activity against cancer cells. However, the cytotoxicity against pancreatic cancer cells and the related mechanisms are unknown. The aim of this study was to evaluate the anti-pancreatic cancer potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Further examination of the biological activities of purified soft coral-derived cembranoids has identified antioxidant and cytotoxic properties of sinularin, 571–573 that 5- epi -sinuleptolide is antiproliferative towards pancreatic tumour cells inducing apoptosis and cell cycle arrest 574 and that crassolide, in models related to the autoimmune disease antiphospholipid syndrome, can suppress dendritic cell maturation and downstream T cell responses. 575 Four new examples of briarane-type diterpenoids, 2-butyryloxybriarane B-3 1336 , 9-acetylbriarenolide S 1337 , briarenolide W 1338 and 12-isobriarenolide P 1339 , were isolated from a Yucatan Peninsula collection of Briareum asbestinum .…”
Section: Cnidariansmentioning
confidence: 99%
“…Further examination of the biological activities of purified soft coral-derived cembranoids has identified antioxidant and cytotoxic properties of sinularin, 571–573 that 5- epi -sinuleptolide is antiproliferative towards pancreatic tumour cells inducing apoptosis and cell cycle arrest 574 and that crassolide, in models related to the autoimmune disease antiphospholipid syndrome, can suppress dendritic cell maturation and downstream T cell responses. 575 Four new examples of briarane-type diterpenoids, 2-butyryloxybriarane B-3 1336 , 9-acetylbriarenolide S 1337 , briarenolide W 1338 and 12-isobriarenolide P 1339 , were isolated from a Yucatan Peninsula collection of Briareum asbestinum .…”
Section: Cnidariansmentioning
confidence: 99%
“…Sustaining high cyclin B1–CDK1 activity resulted in cell arrest in the M phase and caused cell cycle arrest. 5- epi -sinuleptolide also suppressed the expression of cyclin D, which is an important cell cycle regulator throughout the cell cycle [ 82 ]. Ono et al reported that p53 induced G1/S phase or G2/M arrest via p21 inhibition of CDKs [ 83 ].…”
Section: Mechanisms Of Action Of Mnps In Crc and Pcmentioning
confidence: 99%
“…Their results indicated that 5- epi -sinuleptolide induced p21 expression but not p53 expression. Therefore, Tsai et al suggested that 5- epi -sinuleptolide mediates cell cycle arrest through a p53 independent pathway [ 82 ].…”
Section: Mechanisms Of Action Of Mnps In Crc and Pcmentioning
confidence: 99%
“…The genus Sinularia (order Alcyonacea, family Alcyoniidae), composed of about 150 species, 1 a has long been an intensive research subject of marine natural product chemists and has proved to be a rich source of structurally diverse and biologically active terpenoids. 1 b To our knowledge, till now, more than 700 intriguing sesqui- and diterpenoids, some of which showed a wide range of biological activities, including cytotoxic, 2 anti-inflammatory, 3 immunopotentiation, 4 neuroprotective effects, 5 etc ., have been reported from various species of this genus. The complex structural features of Sinularia terpenoids have attracted much attention from natural product chemists, synthetic chemists and pharmacologists as well.…”
Section: Introductionmentioning
confidence: 99%